Nitrogen addition and mowing affect microbial nitrogen transformations in a C4 grassland in northern China - Wang, C.; Butterbach-Bahl, Klaus; He, N.; Wang, Q.; Xing, X.; Han, X. (Wiley, 2015)
Microbial nitrogen (N) transformations play a key role in regulating N cycling in grassland ecosystems. However, there is still little information on how management of semi‐arid grassland such as mowing and/or N fertilizer application affects microbial activity and N transformations. In a field experiment in northern China, N was added at a rate of 10 g N m−2 year−1 as NH4NO3 to mown and unmown plots (4 × 4 m2) and in situ rates of net ammonification (Ramm), nitrification (Rnit) and mineralization (Rmin) were followed at monthly intervals for the vegetation growth periods in the years 2006–2009. In addition, we also measured soil microbial biomass carbon (MBC) and nitrogen (MBN), microbial respiration (MR) and peak above‐ground biomass in August of each measurement year. Driven by the pronounced inter‐annual variability of rainfall, all the properties investigated varied markedly across years. Nevertheless, we were able to demonstrate that over the 4 years N addition significantly stimulated Rnit, Rmin and MBN, on average, by 288, 149 and 11.6%, respectively. However, N addition decreased MBC significantly as well as the ratio of MBC:MBN by, on average, 10 and 23%, respectively, whereas an effect of N addition on MR could not be demonstrated. Mowing decreased MBN, MR and qCO2 significantly by 9, 28 and 24%, respectively, but no effects were found on microbial net N transformation rates and MBC. N addition and mowing interactively affected Ramm and Rmin, and MBN, MBC:MBN. In summary, our results indicate a positive effect of N addition but a negative effect of mowing on microbial N transformation in this C4 grassland in northern China.